Performance-based rewards as a determinant of employee retention among tier-one commercial banks in Kenya - Daudi, Julianna M. (Strathmore University, 2021)
Globally, organizations face a threat of losing talent to competition due to the growth experienced in the world economy (Hay Group, 2015). Further, workers globally are seeking new opportunities and there is emergence of new businesses and labour market is also advancing. Kenya’s banking industry has experienced high turnover rates where employees quit one bank and seek better opportunities in other banks within and outside the country. This is mainly attributed to long working hours, poor leadership, increased workload, poor work environment, insecurity, lack of work-life balance and dissatisfying salaries. These factors, have led to talent flight, where highly skilled employees look for greener pastures in other banks. The general study objective was to establish the performance-based rewards as a determinant of employee retention among tier-one commercial banks in Kenya. Specific objectives were to examine the effects of remuneration, bonuses, job promotion, and recognition on employee retention in tier-one commercial banks in Kenya. Herzberg two factor theory and the expectancy theory was used. Descriptive research design was adopted. The study population comprised 3510 management level employees in the 8 tier-one banks at their headquarters. The Yamane formula was used to calculate the study sample. The sample size of the study was 395 respondents. Multistage sampling technique was used in sample selection. The study collected primary data using a semi-structured questionnaire. The drop and pick later method was used in data collection. A pilot test was done to determine the validity and reliability of the questionnaire. Descriptive statistics which include frequencies, standard deviation and mean helped in analyzing quantitative data. The data was presented in form of tables, pie charts and 3-D graphs. Content analysis was used to analyze data from open questions. The multiple regression analysis helped in establishing the relationship between dependent variable and independent variables. The results were presented in form of tables. The results revealed that remuneration had a statistically significant relationship with employee retention (β = 0.394, P = 0.003) among tier-one commercial banks in Kenya. The study also revealed that bonuses had a statistically significant relationship with employee retention (β = 0.352, P = 0.003). It was established that job promotion had a statistically significant relationship with employee retention (β = 0.347, P = 0.003) among tier-one commercial banks in Kenya. The study revealed a statistically significant relationship (β = 0.362, P = 0.003) between employee recognition and employee retention among tier-one commercial banks in Kenya. The study recommends that commercial banks should ensure that basic pay, commission and performance related pay is integrated its human resources strategies. The study recommends that the commercial should ensure that individual bonuses, team bonuses and company-wide bonuses are part of their employees’ plans to ensure employee retention. The study suggests that commercial banks should consistently make use of job enrichment, advancement in benefits and advancement in designation. The study recommends that commercial banks adopt different recognition methods such as formal recognition, informal recognition and day-to-day recognition. This would assist in ensuring employee retention.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Performance-based rewards; Employee retention; Tier-one commercial banks in Kenya